Question #067a8

1 Answer
Sep 27, 2016

#a_n = a_1+(n-1)d#

Explanation:

Given an arithmetic progression with initial term #a_1# and a difference #d# between successive terms, that is, #a_k = a_(k-1)+d#, then the general term for the #n^"th"# term is given by

#a_n = a_1+(n-1)d#

Proof: (By induction)

Base case: For #n=1#, we have #a_1 = a_1+0d = a_1(n-1)d#

Inductive hypothesis: Suppose that for some integer #k>0#, we have #a_k = a_1+(k-1)d#.

Induction step: We wish to know that #a_(k+1) = a_1+((k+1)-1)d#. Indeed,

#a_(k+1) = a_k + d#

#=a_1+(k-1)d + d# (by the inductive hypothesis)

#=a_1 + kd#

#=a_1+((k+1)-1)d#

Thus, by induction, #a_n = a_1+(n-1)d# for all integers #n>=1#.